Imuno-expressão da metalotioneína em cistos e tumores odontogênicos - Aline Cristina Batista Rodrigues Johann (2009)
Odontogenic cysts and tumours are lesions which originate from tooth-forming tissues and present different biological behaviors. Metallothionein (MT) is related to homeostasis of metals, regulation of cellular differentiation and proliferation, and inhibition of apoptosis. In odontogenic cysts and tumours, MT could have a role in the regulation of cellular proliferation and differentiation, and in inhibition of apoptosis, though interfering in their biological behavior. The aims are to evaluate and to compare MT expression among: 1) odontogenic cysts and keratocystic odontogenic tumour (KOT); 2) KOT associated with nevoid basal cell carcinoma syndrome (NBCCS) and not associated one; and 3) benign odontogenic tumours. Also, the correlation of MT immunoexpression with cellular proliferation and inflammation was assessed. Cases of radicular cyst (RC), dentigerous cyst (DC), KOT (primary, associated or not with NBCCS), orthokeratinized odontogenic cyst (OOC), solid ameloblastoma (SAB plexiforme and follicular types), squamous odontogenic tumour (SOT), adenomatoid odontogenic tumour (AOT), calcifying cystic odontogenic tumour (CCOT) and calcifying epithelial odontogenic tumour (CEOT) were submitted to immunohistochemistry for MT, Ki-67 and PCNA. The index of MT (IMT), Ki-67 (IK) and PCNA (IP) was calculated. Counting of inflammatory cells was also performed in odontogenic cysts, KOT and SAB. Odontogenic cysts and KOT were grouped into group A (weak to moderate inflammation) or group B (strong). BioEstat® 4.0 was used for statistical analysis. The highest IMT was observed in RC followed by DC, KOT and OOC. Differences were not significant only between RC and DC. The highest IK was observed in KOT followed by OOC, RC, and DC. Differences were significant between KOT and all other lesions. IMT was inversely correlated with IK in KOT and OOC, but positively in RC and DC. No difference of IMT was observed between groups A and B. IMT was variable among lesions and this can be attributed to its role in cellular differentiation and inhibition of apoptosis. The correlation of MT with cellular proliferation seems to be inverse in KOT and OOC, but direct in RC and DC. IMT do not seem to be modified by inflammation. Non-syndromic KOT showed a higher IMT than syndromic ones, but IK was similar. An inverse correlation between IMT and IK was noted. No difference in IMT was observed between groups A and B. Syndromic KOT showed a different immunofenotype with lower MT than non-syndromic ones, which may contribute more in apoptosis than in cellular proliferation. Besides, IMT did not seem to be influenced by inflammation. In benign odontogenic tumours, the highest IMT was observed in SAB, followed by CCOT, SOT, AOT, and it was absent in CEOT. Significant differences were observed between SAB and the lesions SOT, AOT and CCOT. The highest IK was observed in SAB, followed by SOT, AOT, CEOT, and CCOT. The highest IP was observed in SAB, followed by SOT, CEOT, CCOT and AOT. For IK and IP, significant differences were observed between SAB and AOT, SAB and CCOT. A positive correlation between IMT and IK, and IMT and IP was observed in SAB, SOT and CCOT, but the correlation was inverse in AOT. In SAB, a positive correlation between inflammation and IMT was noticed. This variable IMT among lesions may possibly be due to its role in cellular differentiation and/or biological behavior. The correlation between MT and cellular proliferation seems to be inverse in AOT, but direct in SAB, SOT, and CCOT. In SAB, IMT seems to be influenced by inflammation.The present study reveals differences in MT immunoexpression among the odontogenic lesions evaluated. This finding can be associated with differences in cellular differentiation and apoptosis. Correlation of IMT and cellular proliferation did seem to be positive in odontogenic cysts and tumours, except in KOT, OOC and AOT. Besides, inflammation did not modify MT immunoexpression in odontogenic cysts and KOT. A positive correlation was observed between inflammation and MT expression in SAB.